1997
DOI: 10.1103/physrevc.56.1511
|View full text |Cite
|
Sign up to set email alerts
|

Low-energy extensions of the eikonal approximation to heavy-ion scattering

Abstract: We discuss different schemes devised to extend the eikonal approximation to the regime of low bombarding energies (below 50 MeV per nucleon) in heavy-ion collisions. From one side we consider the first-and second-order corrections derived from Wallace's expansion. As an alternative approach we examine the procedure of accounting for the distortion of the eikonal straight-line trajectory by shifting the impact parameter to the corresponding classical turning point. The two methods are tested for different combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 23 publications
2
33
0
Order By: Relevance
“…Wallace explicitly derived the first three orders of the correction [24][25][26]. However, our analysis, like others [27][28][29], has shown that only the first order is significant; it is given by…”
Section: Wallace's Correctionmentioning
confidence: 67%
See 4 more Smart Citations
“…Wallace explicitly derived the first three orders of the correction [24][25][26]. However, our analysis, like others [27][28][29], has shown that only the first order is significant; it is given by…”
Section: Wallace's Correctionmentioning
confidence: 67%
“…The encouraging results obtained in Ref. [29] for structureless nuclei suggest that it can be generalized to collisions involving more complex structures such as halo nuclei.…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations